2021
DOI: 10.1037/pst0000366
|View full text |Cite
|
Sign up to set email alerts
|

The alliance–outcome association in the treatment of adolescent depression.

Abstract: A growing body of research has consistently demonstrated a relationship between alliance and treatment outcomes in youth psychotherapy. However, past research often suffered methodological issues that prevented detailed investigation of temporal relationships between alliance and symptomatology. The current study explored the directions of effect between alliance and outcome by examining the associations between early alliance and subsequent outcome while controlling for patients' baseline severity and prior s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 64 publications
(138 reference statements)
1
15
0
Order By: Relevance
“…As expected, we found that the alliance ratings of both adolescents and therapists were quite stable over time. This adds to the previously scarce evidence on the development and change over time of alliance with adolescents [ 25 , 64 ], supports the previous findings that the alliance is formed at an early stage of treatment [ 22 , 30 , 31 ], and raises the importance of focusing on building the relationship at the very beginning of treatment. According to this finding, the alliance measurement timing would not be of great importance in terms of predicting the treatment outcome.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…As expected, we found that the alliance ratings of both adolescents and therapists were quite stable over time. This adds to the previously scarce evidence on the development and change over time of alliance with adolescents [ 25 , 64 ], supports the previous findings that the alliance is formed at an early stage of treatment [ 22 , 30 , 31 ], and raises the importance of focusing on building the relationship at the very beginning of treatment. According to this finding, the alliance measurement timing would not be of great importance in terms of predicting the treatment outcome.…”
Section: Discussionsupporting
confidence: 83%
“…However, as Karver et al (2018) [ 24 ] highlighted, high ratings on average might suggest that rating of alliance at the midpoint or lower by adolescents should be noted as an alarming sign. One interpretation could also be that the effect of the assessment sessions before the actual therapy started was so significant in terms of early symptom improvement that it affected the perceived alliance at baseline measurement and throughout the treatment [ 22 ]. Furthermore, adolescents with less severe symptoms might be more open to new positive relationships or more optimistic about the possibility that the therapist understands their situation and will be able to help.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations